Analysis of the Difference Between Stock Performance Before and After the Announcement of Right Issues in Companies Listed on the Indonesia Stock Exchange (IDX) for the 2015 and 2018 Periods: Analisis Perbedaan Antara Kinerja Saham Sebelum Dan Sesudah Pengumuman Right Issue Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2015 Dan 2018 - Mey Regitasari; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the analysis of differences between stock performance before and after the announcement of the right issue in companies listed on the Indonesia Stock Exchange (IDX) for the 2015 and 2018 periods. The sampling method used is the purposive sampling method. The number of companies that were sampled in this study were 10 companies listed on the IDX in the period 2015 and 2018. The data used is secondary data. The data analysis method used in this study is SPSS 23. The results of this study indicate that there is a difference between stock prices before and after the 2015 rights issue. There is a difference between stock prices before and after the 2018 rights issue. There is a difference between stock performance before and after the rights issue. after the right issue period 2015. There is a difference between the performance of the shares before and after the rights issue period 2018.